Facilitating adaptive management in a government program: A household energy efficiency case study. (1st February 2017) - Curtis, Jim; Graham, Alex; Ghafoori, Eraj; Pyke, Susan; Kaufman, Stefan; Boulet, Mark
Abstract: Interim evaluations of government programs can sometimes reveal lower than expected outcomes, leading to the question of how adjustments can be made while the program is still underway. Although adaptive management frameworks can provide a practical roadmap to address this question, a lack of successful learnings and poor implementation have hampered the progress and wider application of adaptive management. Using a case study involving an energy efficiency government program targeting low-income households, this article provides supporting evidence on how adaptive management can be facilitated and applied. Factors such as proactive and responsive leadership, establishing a research-practice interface, and recognizing the skills, expertise, and contributions of multiple stakeholders guided adjustments to the program, and later paved the way for longer-term organizational learning that impacted how other programs are delivered. Implications for knowledge and practice, and a discussion of the challenges faced in the program, advance current thinking in adaptive management. Highlights: A case study of adaptive management in a government home energy program is provided. Proactive leadership and a research-practice interface were critical to the process. Program and field staff knowledge were key to implementing the changes. Adaptive management principles now implemented across all new programs.